Spray deposition effects on superhydrophobicity and durability of nanocoatings. Issue 2 (1st June 2014) - Steele, Adam; Loth, Eric; Yeong, Yong Han; Davis, Alexander; Bayer, Ilker S.
Abstract : Superhydrophobic coatings fabricated by spray deposition techniques have recently gained prominence, especially in applications where large surface area coatings are desired. While the spray-casting heights and air pressures can have substantial influence on the superhydrophobicity and wear durability of the coatings, the effects have not been previously investigated in detail. To address this lack of knowledge, this study sought to systematically investigate these effects for polyurethane clay–fluorine nanocomposite coatings in terms of water contact angle, roll-off angle and mechanical linear abrasion. The results showed that coatings fabricated at high spray-casting heights and low air pressures (longer droplet flight time) were more superhydrophobic than the coatings fabricated at low spray-casting heights and high air pressures (shorter droplet flight time). However, the later coatings were remarkably more resistant to strong linear abrasion as compared to the former. By balancing these application parameters, the authors showed that a combination of durability and superhydrophobicity can be achieved.